Fatigue Life of Extended Hollobolt Connection in Concrete Filled Tube - Abd Rahman, Norashidah; Tizani, Walid (International Journal of Integrated Engineering, 2013)
Studies on the performance of blind bolt connections have been carried out by many researchers. A number of recent studies of new blind bolted connection system have been proposed. The system uses the so called Extended Hollobolt fastener to connect the concrete filled tubular columns. The strength performance of this system has been investigated under both monotonic and cyclic loading. However, the performance of such connections under fatigue loading is still unknown. Therefore, a study to investigate the fatigue performance of Extended Hollobolt was proposed. The main objective of this study is to provide a better understanding of the fatigue life of the proposed blind bolt, consequently provides the design guidance for Extended Hollobolt connection in concrete filled tube. A number of tests were conducted to determine the effect of the frequency and the level of stress range loading on the behaviour of the Extended Hollobolt. The tests were used grade 8.8 bolts subjected to tension. Results show that the frequencies between 0.2 Hz to 5 Hz does affect fatigue life and the stress-range versus fatigue life behaviour of Extended Hollobolt follows the expected pattern of behaviour of standard bolts. The test results of Extended Hollobolt under different stress range then further compared to the normative regulation Eurocode 3. The fatigue life or behaviour of Extended Hollobolt is found to be higher than the theoretical curve of Eurocode 3. Meanwhile, the failure mode of Extended Hollobolt is similar to the standard bolt which is a very positive outcome for blind bolt. However, fatigue life for standard bolt appears to be higher.